TINJAUAN KONSTITUSIONAL KEDUDUKAN MENTERI KOORDINATOR PADA SISTEM KETATANEGARAAN INDONESIA PERSPEKTIF SIYASAH DUSTURIYAH - Lena Puspita Sari; Masril Masril (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2021)
Abstract: This study aims to answer the two problems studied, namely: (1) Is the position of the coordinating minister in the Indonesian constitutional system constitutional, (2) How is the position of the coordinating minister reviewed based on Siyasah Dusturiyah. The method used is normative legal research with systematic and functional legal interpretation methods using inductive logic analysis of legal materials so that it can be seen how the position of the coordinating minister in the Indonesian constitutional system and siyasah dusturiyah perspective. From the results of the research, it was found that, (1) The position of the Coordinating Minister in the Indonesian constitutional system is because the State Ministers referred to in the 1945 Constitution of the Republic of Indonesia are all types of Ministerial positions, namely the Coordinating Minister, the Minister leading the department, and the State Minister who not leading a department, all of them are State ministers who have the same position, namely as assistant to the president in carrying out state governance. In Indonesia, there are currently four (4) areas of the Coordinating Ministry, whose explanations are as follows: Coordinating Ministry for Economic Affairs, Kemenko POLHUKAM, Kemenko Maritime and Investment, Kemenko PMK. In the Islamic constitutional system, based on the study of siyasah dusturiyah, the state ministry institution is known as wizarah. A person who is in charge of carrying out Wizarah's duties is called a Wazir who in his position and authority can be equated or have the same meaning as the coordinating minister or minister of State in the context of the current Indonesian government. Keywords: Position, Coordinating minister, Indonesian State Administration, Siyasah Dusturiyah.